(untitled) (Costa Rican Journal of Guidance & Counseling, 2025)
The main objective of the Academic Conference on Guidance “UNA oportunidad: perspectivas vocacionales” (JAO-UNA) was to strengthen new ways of approaching vocational guidance, offering innovative strategies to face the challenges in various work contexts. The event used a participatory methodology that included conferences, talks, workshops, and teamwork activities, promoting interaction and the exchange of knowledge among attendees, both in person and through virtual environments. This facilitated a dynamic and accessible approach, ensuring diverse participation at a national level due to the combination of the semi-presential modality. The event was attended by prominent Guidance professionals (both national and international), as well as from other disciplines, addressing essential topics such as theoretical updating, employability, emerging contexts, and the use of technologies in the field of vocational guidance. As a result, it was possible to enhance the skills and knowledge of the participants, providing them with practical tools to face current challenges in their respective work fields. The conclusions underlined the positive impact of this type of events in the development and strengthening of the guidance discipline, promoting the comprehensive and contemporary update on vocational guidance in Costa Rica. This addresses key theories and approaches, assuming a critical perspective of its application in the national context and deepening the development of guidance for the fulfillment of the Sustainable Development Goals of the UNESCO 2030 Agenda.